Recent Trends in Porang Research via Bibliometrics Analysis Approach - Jatmiko Eko Witoyo; Panggulu Ahmad Ramadhani Utoro; Eva Niâ€™maturohmah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Porang is a native Indonesian plant with many benefits and has been widely studied by researchers in Indonesia. However, bibliometrics analysis of porang research is still limited. So, this study aims to establish a bibliometric analysis to know the recent trends in porang research. Data were taken from Scopus using Publish or Perish (PoP) software from 2012 to 2022 and processed further using Microsoft Excel and VOSViewer to determine the bibliometric mapping of porang research. The information on publication trends, authors, keywords, journal sources, numbers of publications, author productivity, and citations was analyzed descriptively. The 164 articles were retrieved from the Scopus database using PoP software from 2012 to 2022. The tendency for the number of publications was increased throughout the observation period, with the highest of annual publications in 2022 with 44 articles. Different trends are shown in the fluctuating number of citations each year, and the highest number of citations was found in 2014, with 91 citations. Food Research, Journal of Tropical Life Science, and IOP Conference Series: Earth and Environmental Science are the journals and conference papers that publish the most articles related to porang research, with 4, 4, and 43 articles, respectively, with Wardhani being the most productive as the first author. The â€œglucomannanâ€, â€œAmorphophallus muelleri" and â€œAmorphophallus oncophyllusâ€ were the most title keyword in porang research, with 35, 18, and 18 occurrences, respectively.